2017
DOI: 10.3390/nano7070192
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Highly Sensitive Thymine Sensor for Mercury Ion Detection Based on Surface Enhanced Raman Spectroscopy and the Mechanism Study

Abstract: Mercury ion (Hg2+) is recognized as one of the most toxic metal ions for the environment and for human health. Techniques utilized in the detection of Hg2+ are an important factor. Herein, a simple thymine was successfully employed as the surface enhanced Raman spectroscopy sensor for Hg2+ ion detection. The limit of detection (LOD) of the developed sensor is better than 0.1 nM (0.02 ppb). This sensor can also selectively distinguish Hg2+ ions over 7 types of alkali, heavy metal and transition-metal ions. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…(W. Wu et al, 2015) neurological disorders. A disposable SERS substrate developed by Yang et al, (H. Yang et al, 2017), as shown in Figure 24, by the deposition of thymine for simultaneous detection of Hg 2+ and Pb 2+ ions in drinking water employing oligonucleotide functionalized gold coated polystyrene microspheres (PSMPs). The LoD of the fabricated substrate was found to be 0.1ppb for Hg 2+ ions, which is far lower than the limit prescribed by the World Health Organization (WHO) (Guo et al, 2023).…”
Section: Heavy Metals and Other Small Moleculesmentioning
confidence: 99%
“…(W. Wu et al, 2015) neurological disorders. A disposable SERS substrate developed by Yang et al, (H. Yang et al, 2017), as shown in Figure 24, by the deposition of thymine for simultaneous detection of Hg 2+ and Pb 2+ ions in drinking water employing oligonucleotide functionalized gold coated polystyrene microspheres (PSMPs). The LoD of the fabricated substrate was found to be 0.1ppb for Hg 2+ ions, which is far lower than the limit prescribed by the World Health Organization (WHO) (Guo et al, 2023).…”
Section: Heavy Metals and Other Small Moleculesmentioning
confidence: 99%
“…The results revealed that the Hg 2+ ion sensor designed in this study had a detection limit and linearity comparable to those of recently reported sensors. [33][34][35][36][37][38][39] Table 1 shows the reported LOD values for detecting Hg 2+ ion using thymine-Hg 2+ -thymine pair strategies.…”
Section: Dependence Of Qcm Sensor Response On Hg 2+ Ion Concentrationmentioning
confidence: 99%
“…Table shows examples of plasmonic‐nanomaterials used in heavy metal detection. Mercury species are among the most toxic pollutants for which SERS vestigial detection is of great interest but at the same time is quite challenging . Indirect methods for SERS detection of Hg 2+ have been described which use Raman reporters and also the T‐Hg 2+ ‐T base pair (T: thymine) approach (Figure ) .…”
Section: Sers and Water Quality Analysismentioning
confidence: 99%